The Effectiveness of the Application M3 Board Learning Media (Mean, Median, and Mode) in Class VIII Statistics Materials at Lekok NU Middle School: Indonesia - Lailiyah, Nisfatul; Zuhri, Zainullah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to determine the effectiveness of applying M3 board media (Mean, Median, Mode) in Class VIII Statistics Materials at Lekok NU Middle School. This type of research is quantitative research. The research results show that: 1) The individual analysis results show the effect of using M3 board media on student learning outcomes in class VIII SMPNU Lekok. This is proven through the results of the independent sample t-test showing a significance value (2-tailed) 0.001 <0.05. Therefore, the hypothesis (Ho) is rejected, and the hypothesis (Ha) is accepted. 2) Student activities related to learning from the aspects observed are categorized as active. This is indicated by the acquisition of an average percentage of students' positive activity, namely 96.2% being active in learning mathematics according to predetermined standards, reaching 75% of students being actively involved in the learning process. 3) The average percentage of students positively responding to learning using the M3 board media is 81.13%. This is classified as a positive response as determined by the standard, reaching 75%. 4) The effectiveness of the media in research is seen in student learning outcomes, student activities, and student responses. The results of the descriptive and inferential analysis of the three effectiveness indicators have been fulfilled, so learning using the M3 board media effectively teaches mathematics to class VIII students of SMPNU Lekok.